Impact Report 2022-2023 - 4Korners (2023)

Améliorer la santé et le bien-être des aînés d’expression anglaise vivants dans les Laurentides au Québec - Helou, Rola; Finch, Lois; Richardson, Mary (4Korners, 2022)
La présente évaluation des besoins a été réalisée à la demande du Réseau communautaire des Laurentides 4Korners, un organisme caritatif canadien enregistré qui a été fondé en 2005 dans le but de faire connaître aux citoyens des Laurentides les programmes et les services qui répondent à leurs besoins dans un environnement sécuritaire et inclusif. Elle a pour objectif de déterminer les besoins de la population âgée d’expression anglaise des Laurentides et de vérifier si ces besoins sont présentement satisfaits. Cette évaluation a été menée par le Conseil scolaire des Premières Nations en éducation des adultes, en collaboration avec la firme de consultants S.O.A.R. Solutions. Les travaux ont été réalisés sous la supervision du Comité d’évaluation des besoins des aînés (SNAC), lequel est composé de membres du personnel de 4Korners, du Elders’ Community Worker du Centre de santé Kanesatake, de bénévoles et de consultants en projets du Conseil scolaire des Premières Nations en éducation des adultes.

Improving the Health and Well-being of English-speaking Seniors in the Laurentians, Québec : A Needs Assessment - Helou, Rola; Finch, Lois; Richardson, Mary (4Korners, 2022)
This needs assessment was commissioned by the 4Korners Laurentian Community Network, a registered Canadian charitable organization founded in 2005, which connects individuals of the Laurentians with programs and services to meet their needs in a secure and inclusive environment. The objective was to identify the needs of the aging English-speaking population in the Laurentians and to determine if they are currently being met. The First Nations Adult Education School Council conducted the assessment in partnership with S.O.A.R. Solutions, a consulting firm. The work was overseen by a committee (the Seniors’ Needs Assessment Committee, SNAC), made up of 4Korners employees, volunteers, the Elders’ Community Worker from the Kanesatake Health Center and project consultants from the First Nations Adult Education School Council.

Impact Report 2021-2022 - 4Korners (2022)

Rapport d'impact 2021-2022 - 4Korners (2022)

Impact Report 2020-2021 - 4Korners (2021)

Rapport d'impact 2020-2021 - 4Korners (2021)

Impact Report 2019-2020 - 4Korners (2020)

Profil des jeunes anglophones des Laurentides 15 à 29 ans - 4Korners (2020)
Selon les données publiées par l’Institut de la statistique du Québec en 2020, la population vivant dans les régions administratives de la province a considérablement changé de 2019 à 2021 en raison des répercussions sociales directes de la pandémie de COVID-19 et de ses conséquences sur la migration, la mobilité, l’attractivité de la main-d’oeuvre, la conciliation travail-famille, les habitudes de vie et les loisirs. Ainsi, on estime que 632 000 habitants vivaient dans la région des Laurentides au 1er juillet 2020, marquant une augmentation de 17,7 % pour l’année 2019-2020; ce pourcentage est plus élevé que le taux moyen de l’ensemble de la province (8,5 %) pour cette année. De fait, il est important de souligner que cette région présente la plus forte augmentation depuis le début de la pandémie en mars 2020.

Profile of Laurentian English-speaking Youth 15-29 - 4Korners (2020)
According to data published by the Institut de la statistique du Québec in 2020, the population living in the administrative regions of the province has significantly changed between 2019 and 2021, being directly affected by the social impacts caused by the COVID-19 pandemic and its implications for out-migration, mobility, workforce attractivity, work/life balance, lifestyle habits and leisure activities. As a result, it is estimated that 632,000 inhabitants were living in the Laurentian region as of July 1, 2020. This represents an increase of 17.7% for the year 2019-2020, which is higher than the average rate across the province (8.5%) for that year. In fact, it is important to highlight that this region presents the largest increase since the outbreak of the pandemic in March 2020.

Rapport d'impact 2019-2020 - 4Korners (2020)

Annual Report 2019-2020 : Learning in the Next Decade of Education - Leading English Education and Resource Network (LEARN) (2020)

Impact Report 2018-19 : English Community Services & Support - 4Korners (2019)

Rapport d'impact 2018-19 : Services et soutien pour la communauté anglophone - 4Korners (2019)

Annual Report 2018-2019 - Leading English Education and Resource Network (LEARN) (2019)

Impact Report 2017-18 : English Community Services & Support - 4Korners (2018)

Adaptation Initiative Project Guide 2018-2023 - Community Health and Social Services Network (CHSSN) (2018)
Keywords: Official Language Minority Community (OLMC)

L'initiative d'adaptation : guide des projets 2018-2023 - Community Health and Social Services Network (CHSSN) (2018)
Keywords: Official Language Minority Community (OLMC)

David Graham - Member of Parliament for Laurentides-Labelle - Graham, David (2018)

Annual Report 2017-2018 : Leading the Way - Leading English Education and Resource Network (LEARN) (2018)

General By-Laws of The 4 Korners Family Resource Centre - 4Korners (2017)

Annual Report : 2016-2017 - 4Korners (2017)

Annual Report 2016-2017 - Leading English Education and Resource Network (LEARN) (2017)

CLC Chronicles 2015-2016 - Leading English Education and Resource Network (LEARN) (2016)

Year-End Report - Leading English Education and Resource Network (LEARN) (2016)
The Leading English Education and Resource Network (LEARN) is a non-profit organization that serves the public, private, anglophone and aboriginal Youth and Adult Education sectors of Québec. We bring together the expertise and efforts of educators, students, parents and partners in our community to cultivate success for all learners.

Annual Report : 2015-2016 - 4Korners (2016)

English Language Services Directory: Laurentians Region : 2016 - 4Korners (2016)

Provincial Resource Team Report 2015-2016 - Leading English Education and Resource Network (LEARN) (2016)
Over the last ten years, English schools in Quebec have increasingly embraced the dual role of supporting student perseverance and contributing to the vitality of their English-speaking communities. With more than 80 schools and adult education centres across the province now part of the Community Learning Centre (CLC) network, it is evident that School Boards are adopting a new way of thinking about school and community partnerships. This “integrated focus on academics, services, supports and opportunities leads to improved student learning, stronger families and healthier communities. Schools become centers of the community”
Keywords: Official Language Minority Community (OLMC)

Annual Report : 2014-2015 - 4Korners (2015)

CLC Initiative Annual Report of Activities - Leading English Education and Resource Network (LEARN) (2015)
Keywords: Official Language Minority Community (OLMC)

2013-2014 Annual Report of CLC Activities - Leading English Education and Resource Network (LEARN) (2014)
Keywords: Official Language Minority Community (OLMC)

Annual Report : 2013-2014 - 4Korners (2014)

Community Learning Centres : Changing Lives and Communities Annual Report of Activities - Leading English Education and Resource Network (LEARN) (2013)
This year the 37 Community Learning Centres across Quebec worked collaboratively with more than 700 local, regional, provincial, and national partners, to leverage in excess of $3 million of in-kind services and resources to serve their schools and communities. CLCs are doing more than just leveraging resources; they are changing lives and communities. They serve as a place for education and community development, and have become an important part of collaborative community change efforts. The stories and best practices highlighted in this annual report capture the essence of the initiatives being implemented by CLCs to achieve change and progress in English speaking communities across Quebec. Highlights of the activities undertaken in 2012-2013 begin with how one of our most important stakeholder groups, our teachers, are engaging with our initiative. The Community-Based Learning approach is just one example of the many strategies CLCs are adopting to impact students and develop a culture of lifelong learning. This year’s activities also included many examples of in-school and after-school activities in which CLC students are learning about incorporating healthy living options into their lives as well learning about aboriginal culture and building relationships between aboriginal and non-aboriginal communities. CLCs mobilize community and partner support to address current and important needs in our schools, including improving school climate and reducing bullying. Their activities for adults and seniors demonstrate to students that learning truly is a lifelong process. Engaging parents before their children have even entered school and continuing to find ways to connect and support parents throughout school life is an ongoing and important part of our work.

June 13, 2013 - Leading English Education and Resource Network (LEARN) (2013)

Annual Report : 2012-2013 - 4Korners (2013)

Annual Report : 2011-2012 - 4Korners (2012)

Annual Report : 2010-2011 - 4Korners (2011)

Annual Report : 2009-2010 - 4Korners (2010)

2009-10 Annual Report - Leading English Education and Resource Network (LEARN) (2010)
In a province as vast as Quebec, and with schools and school boards scattered over an enormous geographic expanse, the notion of bringing people together to create a COMMUNITY of collaboration may appear daunting, if not impossible. In reality, when people share similar interests and common goals, those physical impediments can quickly disappear. This is especially true when the ultimate objective is the academic success of our children in elementary and high schools. LEARN’s focus is to serve as a catalyst and facilitator for the creation of communities of collaboration composed of educators, parents and students across the province. It is our organization’s objective to make every effort possible to get the well-intentioned forces within the English educational milieu together to share the wealth of knowledge and experience that resides there.

Rapport Annuel 2009-2010 - Leading English Education and Resource Network (LEARN) (2010)
Dans une province aussi vaste que le Québec, où les écoles et les commissions scolaires sont dispersées sur une immense étendue géographique, la notion de rassembler les gens pour en faire une COMMUNAUTÉ de collaboration semble un obstacle gigantesque, sinon insurmontable. Dans la réalité, les gens partagent des intérêts similaires et des objectifs communs et cette notion d’impossibilité physique s’estompe rapidement. Cette évolution est particulièrement vraie quand l’objectif ultime est la réussite scolaire de nos enfants au niveau des écoles élémentaires et secondaires. LEARN a pour objectif de servir de catalyseur et de facilitateur pour la création de communautés de collaboration réunissant les éducateurs, les parents et les élèves à l’échelle de la province. L’objectif de notre organisation est de déployer tous les efforts possibles pour réunir les forces positives du milieu éducatif anglophone afi n de contribuer au partage des connaissances et des expériences disponibles au sein de notre communauté.

Programme de responsabilité sociale de l’entreprise / Corporate Social Responsibility Program - 4Korners